The multitude of aphantasia subtypes and their respective cognitive differences and pathological considerations: a review on the merging condition - White, Makenna, author (Colorado State University. Libraries, 2024)
Aphantasia is an emerging condition defined as the lack or absence of voluntary imagery. However, there are wide-ranging individual cognitive profiles due to the condition's heterogeneity. While the metacognition and sensory imagery deficit debate has been resolved in favor of the sensory imagery deficit theory due to the correlation of behavioral correlations with objective measures there is still much debate over the general nature of the condition. Much of this confusion arises from the multitude of subtypes and the complicated nature of mental imagery pathways. Aphantasia as a condition is complicated by the fact that it can be acquired and congenital with congenital aphantasia being made up of many different subtypes. While visual aphantasia, a lack of visual mental imagery, is the most prominently studied type there are also multisensory, deficits in all sense modalities, and combinatorial, deficits in two or more sense modalities. The prevalence of these subtypes makes it more difficult to determine distinct etiologies and a common cognitive profile. Despite this, there are new emerging cognitive theories based on the reverse hierarchy model and scene construction theory attempting to further understanding of the condition. The most comprehensive area of aphantasia study is the cognitive profile which generally shows intact perception, intact abilities on tasks thought to rely on mental imagery, and some deficits in memory, dreaming, and emotional processing. Mixed dreaming evidence in aphantasia research has also led to a debate about whether the condition impacts involuntary imagery in the same way it impacts voluntary imagery though this evidence is unclear. However, some of the emotional processing deficits lead to questions about mental health diagnostics and treatment. Overall, aphantasia as a whole has an overall lack of general research definition and diagnosis leading to conflicting research results. The lack of subtype separation adds to this complication.
College of Veterinary Medicine and Biomedical Sciences.
Keywords: aphantasia; cognition; subtypes; mental imagery